Nilai Kepemimpinan dalam Film Soekarno - Aldo Robbyansyah; Panji Dwi Ashrianto; Senja Yustisia (Jurnal Paradigma, 2018)
The background of the problem in this study discusses the case of leader who abuse their positions by doing corruption